MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN BUDAYA DAERAHKU MELALUI MEDIA QR BOOK DENGANPENDEKATAN CRT DI KELAS V: Penelitian Tindakan Kelas - Gresella Barimbing; Mandra Saragih; Siti Roliah Sari Fatma (STKIP Subang, 2025)
This research is motivated by the low learning outcomes of fifth-grade students at SD Negeri 060857 Medan on the topic Cultural Diversity in My Region. Conventional teaching methods and the lack of culturally relevant learning materials have led to low student engagement and comprehension. The aim of this study is to improve student learning outcomes through the use of QR Book media combined with the Culturally Responsive Teaching (CRT) approach. QR Book is a printed medium enhanced with QR codes that link to instructional videos on cultural topics, while CRT emphasizes teaching that connects with students’ cultural backgrounds.This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 12 fifth-grade students. Data collection instruments included observation sheets, evaluation tests, and documentation.The results showed a gradual improvement in student learning outcomes. The percentage of students who met the learning mastery criteria increased from 33,3% in the pre-cycle to 50% in the first cycle, where interactive PowerPoint was used. In the second cycle, after implementing the QR Book media, mastery increased to 83,3%. These findings indicate that the combination of QR Book and CRT approach effectively enhances student motivation, participation, and learning outcomes.